Characterization techniques for dye-sensitized solar cells. Issue 3 (25th January 2017) - Pazoki, Meysam; Cappel, Ute B.; Johansson, Erik M. J.; Hagfeldt, Anders; Boschloo, Gerrit
Abstract : Further understanding and optimization of dye solar cells towards stable and efficient devices necessitate implementation of the characterization techniques. Abstract : Dye-sensitized solar cells (DSCs) have been widely studied in the last two decades and start to be commercialized in the photovoltaic market. Comprehensive characterization is needed to fully understand and optimize the device performance and stability. In this review, we summarize different characterization methods for dye-sensitized solar cells with liquid redox electrolytes or solid state hole transporting materials, most of which can also be used for similar devices such as perovskite based thin film solar cells. Limitations and advantages of relevant methods for studying the energy levels and time scales involved in charge transfer processes as well as charge transport related characteristic lengths are discussed. A summary of recent developments in DSCs and the importance of measured parameters for the device optimization procedure are mentioned at the end.